The effect of date labels on willingness to consume dairy products: Implications for food waste reduction. (August 2018) - Thompson, Bethan; Toma, Luiza; Barnes, Andrew P.; Revoredo-Giha, Cesar
Highlights: We find limited evidence that WTC differs with date label type. Higher risk perceptions were associated with lower WTC with regard best-before date. Better knowledge was associated with lower risk perceptions and only indirectly with lower WTC. Some consumers have higher WTC as they trust companies to protect themselves. Trust in the credibility of the date label itself was not associated with WTC. Abstract: In the context of national and cross-national efforts to reduce the quantity of food wasted by consumers, there is growing interest in the role of date labelling. Recent proposals by policy makers and the food industry to address dairy product waste have included streamlining date-label application and encouraging the use of best-before dates where possible. In order for these measures to have a positive impact on food waste, consumers must not only know the difference between date types, but also be prepared to act on this information and consume products after the best-before date. Through a survey of 548 Scottish consumers we investigated the relationship between product type, date type, reduced labels and willingness to consume (WTC) dairy products in relation to the both the best-before date and the use-by date. We also examined the factors associated with different levels of WTC products in relation to the best-before date including knowledge, risk perceptions and trust. Our results suggest that on their own, the effect on food waste of applying best-before dates to dairy is likely to be small. In order for such changes to be effective, consumer communication that goes beyond improving expiry-date knowledge and addresses the multifaceted nature of related risk perceptions and conceptions of date-label trust will be required.